Analisis Yuridis Terhadap Tindak Pidana Pemalsuan Dokumen - Humaira R, Khaila; Rizaldi, M. Zaki; Hosnah, Asmak Ul (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The crime of document forgery is one form of crime that has a serious impact on security and trust in various aspects of community life. Juridical analysis of the crime of document forgery is important in an effort to understand the legal basis, the role of law enforcement agencies, and the legal consequences associated with the act. This research aims to explore various legal aspects related to criminal acts of document forgery, including legal definitions, types of document forgery, criminal sanctions applied, and law enforcement efforts carried out by related institutions. Qualitative method with normative legal analysis used to examine various laws, regulations, court decisions, and related literature to understand the juridical aspects related to criminal acts of document forgery. The results of the analysis show the legal complexities involved in handling document forgery cases, including challenges in proof, determination of proportional sanctions, and protection of individual rights. This study provides an in-depth understanding of the legal framework governing the crime of document forgery, as well as providing a foundation for the improvement of law enforcement policies and procedures to increase effectiveness in handling similar cases in the future. Keywords: Criminal Offense, Document Forgery, Criminal Sanctions Abstrak Tindak pidana pemalsuan dokumen merupakan salah satu bentuk kejahatan yang memiliki dampak serius terhadap keamanan dan kepercayaan dalam berbagai aspek kehidupan masyarakat. Analisis yuridis terhadap tindak pidana pemalsuan dokumen menjadi penting dalam upaya memahami dasar hukum, peran lembaga penegak hukum, serta konsekuensi hukum yang terkait dengan tindakan tersebut. Penelitian ini bertujuan untuk menggali berbagai aspek hukum yang terkait dengan tindak pidana pemalsuan dokumen, meliputi definisi hukum, jenis-jenis pemalsuan dokumen, sanksi pidana yang diberlakukan, dan upaya penegakan hukum yang dilakukan oleh lembaga terkait. Jurnal ini dibuat dengan Metode kualitatif analisis hukum normatif yang digunakan untuk meneliti berbagai undang-undang, peraturan, putusan pengadilan, serta literatur terkait untuk memahami aspek-aspek yuridis yang terkait dengan tindak pidana pemalsuan dokumen. Hasil analisis menunjukkan kompleksitas hukum yang terlibat dalam penanganan kasus pemalsuan dokumen, termasuk tantangan dalam pembuktian, penentuan sanksi yang proporsional, dan perlindungan hak-hak individu. Studi ini memberikan pemahaman yang mendalam tentang kerangka hukum yang mengatur tindak pidana pemalsuan dokumen, serta memberikan landasan bagi perbaikan kebijakan dan prosedur penegakan hukum untuk meningkatkan efektivitas dalam menangani kasus-kasus serupa di masa depan. Kata Kunci: Tindak Pidana, Pemalsuan Dokumen, Sanksi Pidana